Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work—Definitions, Dimensions, and Forms. (2014) - , Marisol Sandoval; , Christian Fuchs; , Jernej A. Prodnik; , Sebastian Sevignani; Allmer, Thomas
No abstract available